2023
DOI: 10.1101/2023.08.04.551975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ECM degradation in the stump region induced by Fgf during functional joint regeneration in frogs

Abstract: Previous studies indicated the importance of the reciprocal interactions between residual tissues in the stump and the newly formed blastema for achieving functional joint regeneration after amputation at the joint level in newts. This reciprocal interaction during regeneration was named ″reintegration″. When this reintegration mechanism was evoked inXenopus leavis, regeneration of a functional joint was induced in frogs. Interestingly, degradation of extracellular matrix (ECM) in the remaining joint cartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In the present study, we found that tendon-derived cells that proliferated upon stimulation by FGFs can respond to BMP, differentiating into Sox9-positive chondrocytes; FGF might promote not only cell proliferation but also cellular competency to be able to differentiate into chondrocytes, suggesting that the combination of FGF and BMP is important for the transdifferentiation of chondrocytes from tendonderived cells. Our recent study using Xenopus as a model system suggested that FGF can induce matrix metalloproteinase expression in remaining articular cartilage and that BMP might be secreted from the remaining articular cartilage via ECM degradation (Matsubara et al, 2023). Combining these results, it is postulated that functional joints are regenerated through a scheme similar to that summarized in To validate these in vivo schemes, we are planning to conduct in vivo cell fate tracking using genetically modified Iberian ribbed newts (P. waltl).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that tendon-derived cells that proliferated upon stimulation by FGFs can respond to BMP, differentiating into Sox9-positive chondrocytes; FGF might promote not only cell proliferation but also cellular competency to be able to differentiate into chondrocytes, suggesting that the combination of FGF and BMP is important for the transdifferentiation of chondrocytes from tendonderived cells. Our recent study using Xenopus as a model system suggested that FGF can induce matrix metalloproteinase expression in remaining articular cartilage and that BMP might be secreted from the remaining articular cartilage via ECM degradation (Matsubara et al, 2023). Combining these results, it is postulated that functional joints are regenerated through a scheme similar to that summarized in To validate these in vivo schemes, we are planning to conduct in vivo cell fate tracking using genetically modified Iberian ribbed newts (P. waltl).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, FGF, BMP, and PDGF may function as regeneration inducers during joint regeneration in amphibians. Moreover, in X. laevis, the remaining stump tissues may be activated by signals derived from the blastema to achieve proper tissue connection for functional joint regeneration (Matsubara et al, 2023).…”
Section: Introductionmentioning
confidence: 99%